DAMPAK PENGGUNAAN SMARTPHONE PADA PERILAKU SISWA KELAS XIDALAM PEMBELAJARAN SOSIOLOGI DI MA AL-IKHLAS KUALA MANDOR B - Pitri Sari; Warneri Warneri; Iwan Ramadhan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis thesis entitled "Impact Use of Smartphones In Class XI Student Behaviors MA AL-Ikhlas in Kuala Mandor B". A common problem in this research is "How Impact Use of Smartphones In Class XI Student Behaviors MA Al-Ikhlas in Kuala Mandor B?". The general objective of this research is "Knowing the impact of the use of samrtphone in class XI student behavior MA Al-Ikhlas in Kuala Mandor B". The approach used in this study is a qualitative approach with deskripstif method. Data collection techniques used were observation, interview, and documentation. The informants in this study were teachers and students in grade XI MA Al-Ikhlas in Kuala Mandor B. These results indicate that the impact of the use of smartphones in class XI student behavior there are two sub namely positive and negative impacts. The positive impact of smartphones on the student's behavior is that it can increase knowledge, facilitate communication, expanding a network of friends, and as a medium of entertainment. While the negative impact of the use of smartphones in the student's behavior that makes students lazy to study, interfere with the development, potentially influencing attitudes and behavior and experiencing wastage.Keywords: Impact of use, smartphone, student behavior